Study the Dynamic Behavior of Rotor Supported on a Worn Journal Bearings - Adnan Naji Jamil, Prof. Dr.; Ahmed Abdul Hussein Ali, Ass. Prof. Dr.; Tariq Mohammed, PhD. student (Journal of Engineering, 2015)
In this paper, the effect of wear in the fluid film journal bearings on the dynamic behavior of rotor bearing system has been studied depending on the analytical driven of dynamic stiffness and damping coefficients of worn journal bearing. The finite element method was used to modeling rotor bearing system. The unbalance response, critical speed and natural frequency of rotor bearing system have been studied to determine the changes in these parameters due to wear. MATLAB software was used to find the analytical values of dynamic coefficients of journal bearing. The results of rotor mounted on fluid film journal bearings showed that the wear in journal bearing increases the amplitude of unbalance response and decrease critical speed, stability and the natural frequencies.